Traditional utilization and processing of gewang palm (Corypha utan Lam.) starch in Timor island, Indonesia - Joko Ridho Witono; Yayan Wahyu Candra Kusuma; Beth Paul Naiola (The East Java Biological Society, 2018)
Gewang (Corypha utan Lam.), a palm species, is utilized by villagers as a source of starch in East Nusa Tenggara for daily needs. This study was to describe how local people in Nusa Tenggara produce and utilize gewang starch for their diet, particularly as a rice substitute. The starch is extracted from its trunk and consumed after being cooked with grated coconut. This dish, known as “akarbilan” or “puta’ laka”, becomes the most common food in that area during transition period. Based on our analyses, the nutrition properties of 100 gr gewang starch is composed by water 11.995%, ash 0.518%, fat 0.20%, protein 0.69%, carbohydrate 86.59%, amylose 32.726%, amylopectin 51.11%, glucomannan 12.27%, Calcium (Ca) 100.52 mg, Phosphorus (P) 136.74 mg, Iron (Fe) 3.390 mg, and Vitamin B1 0.108 mg. The results suggested that the nutrition properties of gewang starch almost similar with the sago starch. However, gewang has more prospective potency for food alternative, especially in dry land such as Timor island and adjacent regions in order to build food security in Indonesia.